The APACHE Project - Giacobbe P.; Christille J.-M.; Damasso M.; Cenadelli D.; Carbognani A.; Calcidese P.; Bertolini E.; Bernagozzi A.; Sozzetti A.; Lanteri L.; Lattanzi M.G.; Smart R. (EPJ Web of Conferences, 2013)
First, we summarize the four-year long efforts undertaken to build the final setup of the APACHE Project, a photometric transit search for small-size planets orbiting bright, low-mass M dwarfs. Next, we describe the present status of the APACHE survey, officially started in July 2012 at the site of the Astronomical Observatory of the Autonomous Region of the Aosta Valley, in the Western Italian Alps. Finally, we briefly discuss the potentially far-reaching consequences of a multi-technique characterization program of the (potentially planet-bearing) APACHE targets.